2015
DOI: 10.1007/s00256-015-2134-4
|View full text |Cite
|
Sign up to set email alerts
|

Hill-Sachs lesion location: does it play a role in engagement?

Abstract: The modified biceps angle, as measured on MRI, was significantly higher in patients who demonstrated engagement on physical examination than in those who did not. This supports the theory that the location of the Hill-Sachs lesion may play a role in engagement and may be its most important characteristic when determining its significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Of these shoulders, 27 were from studies of cadaveric specimens and 2,533 were from studies of clinical patients with anterior shoulder instability. When the articles were further broken down by the evaluated imaging modalities, there were 4 articles on ultrasound, 10,19,29,37 5 articles on radiographic imaging, 11,34,36,37,44 10 articles on MRI, 17,[21][22][23]30,35,38,[48][49][50] 12 articles on MRA, 15,24,25,[27][28][29][31][32][33]40,42,46 2 articles on 2D CT, 35,41 7 articles on CTA, 14,18,19,20,22,24,26 and 5 articles on 3D CT 16,39,43,45,47 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these shoulders, 27 were from studies of cadaveric specimens and 2,533 were from studies of clinical patients with anterior shoulder instability. When the articles were further broken down by the evaluated imaging modalities, there were 4 articles on ultrasound, 10,19,29,37 5 articles on radiographic imaging, 11,34,36,37,44 10 articles on MRI, 17,[21][22][23]30,35,38,[48][49][50] 12 articles on MRA, 15,24,25,[27][28][29][31][32][33]40,42,46 2 articles on 2D CT, 35,41 7 articles on CTA, 14,18,19,20,22,24,26 and 5 articles on 3D CT 16,39,43,45,47 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…MRI and MRA. Both studies by Gyftopoulos et al 49,50 reported the sensitivity and specificity of MRI. The ranges were 67% to 72.20% and 70% to 87.90%, respectively.…”
Section: Determining Whether Hill-sachs Lesion Is On or Off Trackmentioning
confidence: 99%
See 1 more Smart Citation
“…Two authors classified HSs on the basis of their position to the bicipital groove: Gyftopoulos et al 13 reported the influence of the biceps angle in MRI and found that diagnostic accuracy was highest for a biceps angle greater than 149°, which resulted in a sensitivity of 70% and specificity of 67%. Workman et al 57 also reported the HS's position to the bicipital groove as a reproducible marker.…”
Section: Discussionmentioning
confidence: 99%
“…To justify the variable recurrence risk between different HS patterns, the concepts of HS ‘engagement’6 and ‘tracking’ were developed 11. The contribution of HSs to glenohumeral instability is hence believed to be dependent on the lesion's size, orientation, location and behaviour in relation to the glenoid rim 12 13…”
Section: Introductionmentioning
confidence: 99%